Impact of Climate Change on Erbil Groundwater Basins (North, Middle and South) - Mustafa, Jwan Sabah; Mawlood, Dana Khider (Transactions on Engineering and Computing Sciences, 2024)
The increasing global temperatures and change in precipitation forms due to the climate change have effect on Earth’s hydrological systems, with significant impact on boundary of groundwater basins. This study provides the present understanding of the impact of climate change on Erbil groundwater basins, emphasizing the variable interactions between climatic variables and groundwater dynamics, the largest groundwater basin in the Middle East, the northern part of Iraq. The study presents how rising temperatures lead to lowering groundwater levels and impact Electrical conductivity (EC) in the study area. This has direct impacts on water resources and keeping sustainable groundwater management in the area. The study aims to determine the main factors that impact Erbil basin resources and propose appropriate solutions to keep these vital resources sustainable. In conclusion, this study presents the interaction between climate change and Erbil basins, determining the need for a best approach and techniques to address the challenges posed by these dynamic environmental changes. Effective water resource management, coupled with most appropriate strategies, is imperative for ensuring the resilience of groundwater systems in the face of ongoing and future climate variability.